2003
DOI: 10.1002/gcc.10152
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of Sézary syndrome

Abstract: Sézary syndrome (SS) is a rare form of erythrodermic cutaneous T-cell lymphoma with hematological involvement and a poor prognosis. At present little is known about the molecular pathogenesis of this malignancy. To address this issue, we analyzed 28 SS cases through the use of molecular cytogenetic techniques. Conventional cytogenetic analysis showed 12 of 28 cases with clonal chromosome abnormalities (43%). Seven cases had aberrations affecting chromosomes 1 and 17; five demonstrated rearrangement of chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 62 publications
12
89
1
Order By: Relevance
“…2,79,80 Recurrent chromosomal translocations have not been detected in SS, but complex karyotypes are common. 86,87 Several studies have identified a consistent pattern of identical chromosomal abnormalities in SS, which was almost identical to that in MF, suggesting that both conditions represent parts of the same spectrum of disease with a similar pathogenesis. 88,89 Chromosomal amplification of the JUNB gene, a member of the activator protein-1 (AP-1) transcription factor complex involved in cell proliferation and T helper 2 (Th2) cytokine expression by T cells, has been identified in SS.…”
Section: Sé Zary Syndromementioning
confidence: 92%
“…2,79,80 Recurrent chromosomal translocations have not been detected in SS, but complex karyotypes are common. 86,87 Several studies have identified a consistent pattern of identical chromosomal abnormalities in SS, which was almost identical to that in MF, suggesting that both conditions represent parts of the same spectrum of disease with a similar pathogenesis. 88,89 Chromosomal amplification of the JUNB gene, a member of the activator protein-1 (AP-1) transcription factor complex involved in cell proliferation and T helper 2 (Th2) cytokine expression by T cells, has been identified in SS.…”
Section: Sé Zary Syndromementioning
confidence: 92%
“…Conventional comparative genomic hybridization studies, together with a literature compilation of 166 mycosis fungoides and SS cases, have not detected 9p21 deletion as a recurrent feature of either mycosis fungoides or SS. 27,29 Several array-based comparative genomic hybridization studies also failed to detect CDKN2A-CDKN2B deletion in patients with either mycosis fungoides or SS. 42,43 For patients with transformed mycosis fungoides, our results agree extensively with those obtained by van Doorn et al 30 using a BAC arraybased comparative genomic hybridization approach with 1-Mb resolution.…”
Section: Discussionmentioning
confidence: 99%
“…26 Conventional cytogenetic and comparative genomic hybridization analysis of 28 SS cases, combined with literature survey of 274 SS karyotypes, did not identify 9p21 loss as a cytogenetic feature of SS. 27 Nor did comparative genomic hybridization studies of both mycosis fungoides and SS cases find 9p21 loss as a recurrent imbalance of these lymphomas. 28,29 However, recent array-comparative genomic hybridization data obtained by the Leiden University group identified 9p21 loss in 41% of patients, with mycosis fungoides associated with lower survival rate.…”
Section: And Gil and Peters 5 )mentioning
confidence: 99%
“…Not surprisingly then, pharmacologic inhibition of STAT3 promotes apoptosis in CTCL [77,[80][81][82]. Cytogenetic gains involving STAT5A and STAT5B or their activation in response to cytokines present within the tumor microenvironment suggests a pathogenic role for other STATs [83][84][85].…”
Section: Immunopathogenesismentioning
confidence: 99%